Risk, safety and sex among male PrEP users: time for a new understanding. Issue 12 (2nd December 2017) - Koester, Kimberly; Amico, Rivet K.; Gilmore, Hailey; Liu, Albert; McMahan, Vanessa; Mayer, Kenneth; Hosek, Sybil; Grant, Robert
Abstract: Recent advances in biomedical HIV prevention have led to optimistic projections of a dramatic worldwide reduction of new infections by 2030. This optimism is counterbalanced by concerns that the protective benefits of one such technology, HIV pre-exposure prophylaxis (PrEP), may be negated by increases in other behaviours that offset these benefits (risk compensation). To contribute to a deeper understanding of concepts of safety and risk in the context of HIV PrEP, we draw on the narrative accounts of 61 male PrEP users who participated in the inaugural PrEP demonstration project: the iPrEx open-label extension study. We conducted in-depth interviews with a purposeful sample of iPrEx participants. Overall, participants did not report significant changes to their sexual practices once they had begun taking PrEP. Rather, participants reported experiencing a sense of relief or reprieve from HIV-related stress. This unburdening of fear did not necessarily lead to condomless sex. Instead, men expressed feeling a sense of security and less free-floating fear of HIV. We contend that no longer living under the threat of HIV is a significant benefit that has not been adequately explored in HIV prevention research.